PENGARUH PELAYANAN PRIMA DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA BENGKEL PT. XYZ (Value : Jurnal Manajemen dan Akuntansi, 2022)
Competition in the automotive business is increasing every year, therefore companies need to improve their marketing performance. This study has three objectives, first, to determine the influence of excellent service on customer satisfaction at the PT.XYZ workshop. Second, to determine the influence of price on customer satisfaction at the PT.XYZ workshop. Third, to determine the influence of excellent service and price on customer satisfaction at PT.XYZ workshop. The sampling method used in this study is simple random sampling and based on the calculation results obtained 51 respondents. The approach used in this research is a quantitative approach with multiple linear regression analysis, coefficient of determination, t test and F test using SPSS version 24 application. The results of this researcsh are excellent service does not have a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, and excellent service and price together have a positive and significant effect on customer satisfaction. Companies need to organize more events that give the perception that customers are benefited in terms of price, such as giving discounts, gifts, vouchers, and others.Keywords: Excellent Service, Price, Customer Satisfaction